Download Factoring Differences of Perfect Squares

Survey
yes no Was this document useful for you?
   Thank you for your participation!

* Your assessment is very important for improving the work of artificial intelligence, which forms the content of this project

Document related concepts

Factorization of polynomials over finite fields wikipedia, lookup

Elementary algebra wikipedia, lookup

History of algebra wikipedia, lookup

Propositional formula wikipedia, lookup

Linear least squares (mathematics) wikipedia, lookup

Magic square wikipedia, lookup

Factorization wikipedia, lookup

Transcript
The Mathematics 11
Competency Test
Factoring Differences of Perfect
Squares
You need to know how to do just one more special factorization for the BCIT Mathematics 11
Competency Test.
Notice that
(u + v)(u – v) = (u + v)(u) + (u + v)(-v)
= (u)(u + v) + (-v)(u + v)
= (u)(u) + (u)(v) + (-v)(u) + (-v)(v)
= u2 + uv – uv – v2
= u2 – v2
So, an expression of the form u2 – v2 (called a difference of two perfect squares) can always
be factored into the form
u 2 − v 2 = ( u + v )( u − v )
The formula in the box is a pattern. The symbols u and v may represent numbers, other
algebraic symbols, or even algebraic expressions. It is the precise pattern which must be
satisfied in each case.
Example 1: Factor 4x2 – y2.
solution:
First, we check, and find that the two terms contain no monomial factors in common. Then, we
note that this is a two-term expression, so the methods for factoring trinomials that were
demonstrated in detail in the previous document in the series are not likely to apply.
Whenever the expression to be factored contains just two terms, it is worth checking to see if the
difference of squares pattern above can be used. You need to identify that the expression has
two important features:
(i) it is a difference of two terms – the second term must be subtracted from the first term. In this
example, we do have a difference of two terms.
(ii) it must be possible to write each of the two terms as a square of some expression. In this
example, we see that
4x2 = (2x)2
and
y2 = (y)2,
so this condition is met.
Matching the parts of this expression with the parts of the pattern in the box above, we get
4x2 – y2 = (2x)2 – (y)2 ⇔ u2 – v2
Thus,
David W. Sabo (2003)
Factoring Differences of Perfect Squares
Page 1 of 3
and
u2 = (2x)2
giving u = 2x
v2 = (y)2
giving v = y
Then
4x2 – y2 = u2 – v2 = (u + v)(u – v) = (2x + y)(2x – y)
or, directly
4x2 – y2 = (2x + y)(2x – y)
as the required factorization.
It is each to check this result directly.
(2x + y)(2x – y) = (2x + y)(2x) + (2x + y)(-y)
= (2x)(2x + y) + (-y)(2x + y)
= (2x)(2x) + (2x)(y) + (-y)(2x) + (-y)(-y)
= 4x2 + 2xy – 2xy – y2
= 4x2 – y2
Thus our factorization checks.
Example 2: Factor 9a4 – 36b2 .
solution:
Again, we check that there are no common monomial factors in the two terms (there are none).
Then, recognizing the possibility that this is a difference of two perfect squares (since this
expression obviously is the difference of precisely two terms), we note that:
9a4 = (3a2)2
and
36b2 = (6b)2
So, each of the two terms are perfect squares. So, we can apply the pattern formula given in the
box above:
and
u2 = (3a2)2
or
u = 3a2
v2 = (6b)2
or
v = 6b
to get
9a4 – 36b2 = (3a2 + 6b)(3a2 – 6b)
You can easily verify by multiplication that this factorization is correct.
David W. Sabo (2003)
Factoring Differences of Perfect Squares
Page 2 of 3
Example 3: Factor 9x2 + 4y2.
solution:
This expression consists of two terms, both of which are perfect squares:
9x2 + 4y2 = (3x)2 + (2y)2
However, it is a sum of two perfect squares rather than a difference of two perfect squares. We
might be tempted to try
?
9 x 2 + 4 y 2 = (3 x + 2y )(3 x + 2y )
thinking that since a minus has become a plus on the left-hand side, perhaps the thing to do is to
change the minus to a plus on the right-hand side. However, we should not simply assume this is
the best we can do and move on, but rather, we must check to see if the assumption made here
is correct. That is easy to do, as usual, by multiplication:
(3x + 2y)(3x + 2y) = (3x + 2y)(3x) + (3x + 2y)(2y)
= (3x)(3x + 2y) + (2y)(3x + 2y)
= (3x)(3x) + (3x)(2y) + (2y)(3x) + (2y)(2y)
= 9x2 + 6xy + 6xy + 4y2
= 9x2 + 12xy + 4y2
which is not the same as the original expression, 9x2 + 4y2.
In fact, there is no way to factor the sum of two perfect squares (without introducing more
advanced mathematical concepts that are well beyond the scope of the BCIT Mathematics 11
Competency Test). So, in answer to this example, we need to simply state that the given
expression cannot be factored.
David W. Sabo (2003)
Factoring Differences of Perfect Squares
Page 3 of 3